Customer Perception of Bandung City Societyon E-Money Usage for the Highway Service Payment - Michael Tanu; Rita Komala Dewi; Heni Iswati (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2018)
E-commerce has been used in many business transactions because of its practicality and easiness for the users. In addition, it also provides easiness in control. The use of electronic money (e-money) as a non-cash payment alternative has a huge potential in decreasing the use of cash money. E-money provides faster and more comfortable transactions compared to the cash money, especially for the small-amount transactions. With e-money, every transaction is simpler, cheaper, and easier both for the buyers and sellers. One of the government interventions has recently been that every highway transaction can only be paid using e-money. This policy has resulted in a various response from the consumers or society at large. This research is aimed at exploring the perception of the consumers or society in Bandung on e-money policy for highway service payment. The method used in this research is a descriptive method. The data collection techniques used are literature study and questionnaire distributed to 100 respondents who ever used e-money in their transaction. The results of this research showed that the implementation of e-money is already good. But, there are some constraints in the aspect of service and technology. Those things are based on the measurement using the basic model of Technology Acceptance Model (TAM).